Dr. Ralph Garber, Canada, President of IASSW 1988 - 1996 - Richard Splane (Social Work and Society, 2005)
A fully revealing portrait of Ralph Garber would require a latter-day Boswell. As ordained, however, an attempt must be made to create a recognizable word picture. And it must give initial attention to the range of influences and factors in Ralph Garber's inheritance and environment that, throughout his life, he experienced, absorbed and utilized in his remarkably creative career.